2019
DOI: 10.3390/ijms20112668
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dual-Specificity Phosphatase (DUSP) Ubiquitination and Protein Stability

Abstract: Mitogen-activated protein kinases (MAPKs) are key regulators of signal transduction and cell responses. Abnormalities in MAPKs are associated with multiple diseases. Dual-specificity phosphatases (DUSPs) dephosphorylate many key signaling molecules, including MAPKs, leading to the regulation of duration, magnitude, or spatiotemporal profiles of MAPK activities. Hence, DUSPs need to be properly controlled. Protein post-translational modifications, such as ubiquitination, phosphorylation, methylation, and acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 102 publications
3
123
1
3
Order By: Relevance
“…DUSPs are classified primarily based on the presence of a kinase-interacting motif (KIM). If a DUSP contains a KIM, then it is classified as a typical MAP kinase phosphatase (MKP) or typical DUSP [55]. An atypical DUSP or MKP does not have a KIM [55].…”
Section: Dual-specificity Phosphatases (Dusps): Regulators Of the Jnkmentioning
confidence: 99%
See 1 more Smart Citation
“…DUSPs are classified primarily based on the presence of a kinase-interacting motif (KIM). If a DUSP contains a KIM, then it is classified as a typical MAP kinase phosphatase (MKP) or typical DUSP [55]. An atypical DUSP or MKP does not have a KIM [55].…”
Section: Dual-specificity Phosphatases (Dusps): Regulators Of the Jnkmentioning
confidence: 99%
“…If a DUSP contains a KIM, then it is classified as a typical MAP kinase phosphatase (MKP) or typical DUSP [55]. An atypical DUSP or MKP does not have a KIM [55]. With the type and domain of DUSPs, a phylogenetic tree was constructed in Figure 4.…”
Section: Dual-specificity Phosphatases (Dusps): Regulators Of the Jnkmentioning
confidence: 99%
“…KLF4 increases the susceptibility of GCs to apoptosis by downregulating Bcl2 expression and promotes LH induced luteal transition of GCs (Choi and Roh, 2018). Dual-specific phosphatases (DUSPs) dephosphorylate MAPKs and thereby inhibiting their activities (Chen et al, 2019). We speculate that PMSG-induced Dusp9 suppresses ERK activation to allow proper development of preantral follicles in wildtype ovaries.…”
Section: Discussionmentioning
confidence: 94%
“…In previous study, the allosteric sites in DUSP3 (VHR) and DUSP10 (MKP5) are reported, and these allosteric sites are surrounded by the N-loop and can affect the phosphatase activity [ 30 , 31 ]. Whether the mutations shown in Tables S1 and S2 participate in the process of cancer development is worth studying because N-loop-containing PTPs regulate several signaling pathways, and the deficiency or downregulation of these PTPs is frequently observed in cancer development [ 32 , 33 ]. Drug development to stabilize the DPN–triloop interaction is a possible strategy to benefit cancer treatment.…”
Section: Discussionmentioning
confidence: 99%